2007
DOI: 10.1175/jpo2956.1
|View full text |Cite
|
Sign up to set email alerts
|

Fully Nonlinear Statistics of Wave Crest Elevation Calculated Using a Spectral Response Surface Method: Applications to Unidirectional Sea States

Abstract: This paper concerns the calculation of the probability of exceedance of wave crest elevation. The statistics have been calculated for broadbanded, unidirectional, deep-water sea states by incorporating a fully nonlinear wave model into a spectral response surface method. This is a novel approach to the calculation of statistics and, as all of the calculations are performed in the probability domain, avoids the need for long time-domain simulations. Furthermore, in contrast to theoretical distributions, the bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Provided the BFI is sufficiently large, results have shown that the deviation from the Gaussian statistics can be more significant than in second-order theory. Recently, similar findings have also been discussed by Gibson et al (2007), who have investigated the wave crest distribution by combining a fully nonlinear wave model with reliability methods, which are used for design and safety assessment of marine structures.…”
Section: Introductionsupporting
confidence: 65%
“…Provided the BFI is sufficiently large, results have shown that the deviation from the Gaussian statistics can be more significant than in second-order theory. Recently, similar findings have also been discussed by Gibson et al (2007), who have investigated the wave crest distribution by combining a fully nonlinear wave model with reliability methods, which are used for design and safety assessment of marine structures.…”
Section: Introductionsupporting
confidence: 65%
“…This follows from the result that the peaks of a Gaussian process are Rayleigh distributed [34]. Similar method was previously used by Gibson et al [35] and Jensen [36]. We look at the peak statistics with no extra sorting related to statistical independence.…”
Section: First Order Reliability Methodsmentioning
confidence: 99%
“…However, they have not been applied to the computation of random directional wave fields over a large spatial domain due to the computational burden. A promising method that allows the prediction of statistical properties of fully nonlinear waves was recently presented by Gibson, Swan & Tromans (2007), who combined the fully nonlinear wave model by Bateman et al (2001) with a spectral response surface method; this study, however, was limited to unidirectional waves. In several studies (see e.g.…”
Section: Introductionmentioning
confidence: 99%